The Effectiveness of Photograph towards Students’ Ability in Writing Descriptive Text - Sarina, Sarina (Maspul Journal of English Studies, 2022)
The purpose of this study is to find out how the media can improve the writing ability of students in eighth grade Mts Muhammadiyah Tongko. The research method used in this study was a pre-experiment. The research subjects were 23 second grade students at MTs Muhammadiyah Tongko. Data collection techniques are used, namely, pre-test was given to students prior to treatment, the treatment was given in the form of making descriptive text about animals, post-test was given after treatment to see the results of the treatment given. The results of his study showed that there was an increase in students' writing performance in the descriptive text using image media. This can be seen from the calculation of the T-Test at 0.00 < 0.05 which to = 6,093 > tt = 2,016 shows a significant result after being given treatment in the form of the use of image media. This shows that by applying image media, students' writing performance in descriptive text and getting ideas can be improved.